2021
DOI: 10.3390/ijerph182312487
|View full text |Cite
|
Sign up to set email alerts
|

A Road Safety-Based Selection Methodology for Professional Drivers: Behaviour and Accident Rate Analysis

Abstract: In this paper, we examine the factors affecting the behaviour of road users and the impact of these factors on professional drivers’ reliability and performance. A professional driver is considered as a driver involved in the processes of driving a vehicle as a matter of his/her business or the transportation of passengers or goods by bus or lorry, with higher liability in terms of road safety and requiring a higher degree of maintained attentiveness, constant concentration, and working capacity. This article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…For example, in Lithuania, the training program for professional drivers has been updated, which will provide an opportunity to acquire a professional qualification that is mandatory throughout the European Union (EU) and to Taking into account the fact that cargo transportation is a complex process, during which the safe transportation of cargo must be ensured, therefore drivers transporting this type of cargo must be trained [7,42]. For example, in Lithuania, the training program for professional drivers has been updated, which will provide an opportunity to acquire a professional qualification that is mandatory throughout the European Union (EU) and to provide cargo and passenger transport services in any EU country [43,44]. The new procedure has been prepared taking into account the proposals submitted by businesses and associations uniting cargo and passenger transport companies, as well as associations of driving training institutions, the main focus of which is safe and economical driving.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Lithuania, the training program for professional drivers has been updated, which will provide an opportunity to acquire a professional qualification that is mandatory throughout the European Union (EU) and to Taking into account the fact that cargo transportation is a complex process, during which the safe transportation of cargo must be ensured, therefore drivers transporting this type of cargo must be trained [7,42]. For example, in Lithuania, the training program for professional drivers has been updated, which will provide an opportunity to acquire a professional qualification that is mandatory throughout the European Union (EU) and to provide cargo and passenger transport services in any EU country [43,44]. The new procedure has been prepared taking into account the proposals submitted by businesses and associations uniting cargo and passenger transport companies, as well as associations of driving training institutions, the main focus of which is safe and economical driving.…”
Section: Discussionmentioning
confidence: 99%
“…et al showed a significant association between driving more than 9.5 hours with the occurrence of road accidents due to continuous driving and fatigue [27]. Zaranka et al also showed that increasing working hours reduced the sleep and rest of truck drivers [28]. However, there is no conclusive evidence for an optimal rest period (other than strenuous physical work) or to support the claim that increasing the rest period offsets the negative effect of extended work shifts [24].…”
Section: Discussionmentioning
confidence: 99%
“…Additional studies also show that fatigue increases the risk of traffic accidents and reduces the ability to control a vehicle, which can lead to serious consequences [36]. Drivers affected by fatigue are more likely to make mistakes while driving, such as driving at inappropriate speeds, crossing lines, frequent braking, or poor reactions to traffic [37].…”
Section: Theoretical Backgroundmentioning
confidence: 99%